Protocol for a randomized controlled trial of Xueshuantong injection on myocardial injury and residual cardiovascular risk in patients with unstable angina - Wang, Yaxing; Liu, Guangyu; Lu, Zhenkai; Xi, Junyu; Feng, Wenye; Ma, Yutong; Lyu, Jian; Xie, Yanming (Frontiers in Cardiovascular Medicine, 2025)
BackgroundUnstable angina (UA) is a critical subtype of acute coronary syndrome (ACS). Myocardial injury is a key determinant of disease progression and long-term prognosis, yet it often persists despite standard therapy. In addition, residual inflammation remains an important risk factor for adverse outcomes. Xueshuantong Injection Lyophilized (XST), derived from Panax notoginseng saponins (PNS), has shown potential to reduce myocardial injury and modulate inflammatory responses in cardiovascular disease, but its efficacy in UA has not been fully evaluated.MethodsThis is a randomized, parallel control, double-blind, small-sample exploratory clinical trail. Participants will be recruited from Xiyuan Hospital, China Academy of Chinese Medical Sciences (Beijing, China). Eligible patients with UA will be randomized into two groups. The intervention group will receive XST 500 mg intravenously once daily for 7 days, and the control group will receive XST 25 mg intravenously once daily for 7 days. The primary outcome is CK-MB at Day 7. Secondary outcomes are cTnT, NT-proBNP, inflammatory/endothelial biomarkers (hs-CRP, IL-6, MMP-9, VEGF, HMGB1), and angina-related parameters (attack frequency, symptom severity).Ethics and RegistrationThe trial has been approved by the Ethics Committee of Xiyuan Hospital and registered in the ITMCTR on March 21, 2025, http://itmctr.ccebtcm.org.cn (No. ITMCTR2025000552).ConclusionThis exploratory study will evaluate the efficacy and safety of XST in reducing myocardial injury and residual risk in UA patients, providing evidence for future large-scale confirmatory trials.